Rui Barbosa: mito, memória e esquecimento - Silva, Wilton Carlos Lima da [UNESP] (Universidade Estadual de Maringa, 2012)
The remembrance of Rui Barbosa has always involved the maintenance of myths fabricated during his lifetime while a reappraisal of his intellectual, literary and political dimensions has been forwarded. Current essay discusses from several bibliographical samples on Brazilian social thought the manner the memory of the lawgiver from Bahia has been appropriated civically and intellectually. A qualitative and quantitative contrast was established between Barbosa’s works published and referred to and those by Joaquim Nabuco, Sílvio Romero and Gilberto Freyre. Oscillations in the evaluation of Barbosa’s works occurred during the 20th century that brought about a decrease in their value and about the memory on the historical subject.

La memoria de Rui Barbosa ha sido un campo para mantener los mitos creados en vida y, al mismo tiempo, permitió un redimensionamiento de su valor intelectual, literario y político. A partir de una muestra de la bibliografía sobre el pensamiento social brasileño, proponemos discutir la forma en que la memoria del jurista bahiano es apropiada de forma cívica e intelectual. Para ello, pretendemos establecer un contraste cualitativo y cuantitativo entre las obras publicadas y referenciadas del jurista y de Joaquim Nabuco, Sílvio Romero y Gilberto Freyre, apuntando oscilaciones valorativas a lo largo del siglo XX que marcaron un ocaso de la obra de Barbosa y de su memoria.

A memória de Rui Barbosa tem sido campo da manutenção de imagens criadas em vida, ao mesmo tempo em que surgiu o redimensionamento de seu valor intelectual, literário e político. Propomos discutir, a partir de uma amostra da bibliografia sobre o pensamento social brasileiro, a forma como a memória do jurista baiano é apropriada de forma cívica e intelectual. Para tanto, pretendemos estabelecer um contraste qualitativo e quantitativo entre as obras publicadas e referenciadas do jurista e de Joaquim Nabuco, Sílvio Romero e Gilberto Freyre, apontando oscilações valorativas ao longo do século XX que marcaram um ocaso da obra barbosiana e da memória do personagem.
Rui Barbosa: myth, memory and forgetfulness
Rui Barbosa: mito, memoria y olvido
Keywords: Rui Barbosa; Political myth; Memory; Intellectual production; Liberalism; Rui Barbosa; Mito político; Memoria; Producción intelectual; Liberalismo; Rui Barbosa; Mito político; Memória; Produção intelectual; Liberalismo